Molecularly Imprinted Polymers for TNT Analogues. Development of Electrochemical TNT Biosensors - Anna Herrera-Chacon; Inmaculada Campos; Lourdes Bottone; Manel del Valle (Proceedings, 2017)
Trinitrotoluene (TNT) is a widely employed explosive compound; for that reason, an [...]